Burn [videorecording (DVD)] - Putnam, Tom; Sanchez, Brenna (Callbox LLC, 2012)
"This riveting and inspiring film captures a year in the life of Detroit firefighters, who are charged with the thankless task of saving a city many have written off as dead. With vast stretches of abandoned buildings, the highest arson rate in the country, and budget crisis of epic proportions, these brave men and women risk injury, disablement, and death to try and make a difference for the city they call home." -- Container.